A Plasmon‐Enhanced SnSe2 Photodetector by Non‐Contact Ag Nanoparticles. Issue 35 (14th July 2021) - Sun, Xiaoli; Sun, Jiamin; Xu, Jinlong; Li, Ziqi; Li, Rang; Yang, Zaixing; Ren, Feng; Jia, Yuechen; Chen, Feng
Abstract: The 2D layered materials are promising candidates for broadband, low‐cost photodetectors. One deficiency of 2D materials is the relatively low absorbance of light, limiting the applications of the 2D photodetectors. Doping of plasmonic nanoparticles into 2D materials may enhance the optical absorbance owing to the localized surface plasmonic resonance (LSPR) effect; however, considerable defects may be introduced into the 2D materials at the same time, resulting in certain degradation of device performance. Here, a novel design of 2D photodetectors with enhanced photoresponsivity by non‐contact plasmonic nanoparticles (NPs) is proposed, consisting of a hybrid structure of few‐layer SnSe2 transferred a fused silica (SiO2 ) plate with embedded Ag NPs. The system of Ag NPs‐in‐SiO2 shows strong LSPR effect with significantly enhanced optical absorption, acting on SnSe2 in a non‐contact configuration. Benefiting from well‐preserved intrinsic features of SnSe2 and LSPR effect, the responsivity of the photodetector is enhanced by 881 times with the bias voltage of 0.1 V, which is superior to previously reported results of plasmon‐enhanced 2D photodetectors. Moreover, the SiO2 with embedded Ag NPs is recyclable and can be easy to be recombined with different 2D materials. This work offers additional strategy for development of efficient, low‐cost 2D photodetectors by using plasmonic NPs. Abstract : A novel 2D photodetector is prepared by ion implantation and CVD, improving the photoresponsivity combined the scattering, plasmon resonance energy transfer and local electromagnetic field enhancement mechanism. The responsivity of the SnSe2 ‐based photodetector is enhanced by up to 881 times at room temperature with the bias voltage of 0.1 V via non‐contact plasmonic nanoparticles.